Comparison of organic acids supplementation on the growth performance, intestinal characteristics and morphology, and cecal microflora in broilers fed corn-soybean meal diet - Hao Yang Sun; Hong Bin Zhou; Yang Liu; Yue Wang; Cheng Zhao; Liang Mei Xu (Animal Bioscience, 2022)
Objective The aim of this study was to compare the effects of three kinds of organic acid (OA) products on the growth performance, intestinal characteristics and morphology, and cecal microflora in broilers fed a corn–soybean meal meal diet. Methods A total of 420 one-day-old male Cobb 500 broilers with an average initial body weight of 49.11±1.02 g were used in this 42-day experiment. Birds were randomly allotted to one of five treatments (7 replicates with 12 birds per replicate). Treatments consisted of negative control (NC), basal diet; positive control (PC), basal diet+100 mg/kg of Aviramycin; OA1, basal diet+500 mg/kg of OA product 1; OA2, basal diet+1,000 mg/kg of OA product 2; and OA3, basal diet+1,200 mg/kg of OA product 3. Results The results indicated that OA product addition had no effect on growth performance parameters, such as body weight gain, feed intake, and feed conversion ratio, from days 1 to 14, 15 to 28, and 0 to 42, or on the pH values of the intestine, intestinal weight, or intestinal weight to body weight ratio. The intestinal morphology in terms of villus height and crypt depth were affected by dietary supplementation of OA products, respectively. Furthermore, dietary addition of OAs had positive influences on the maintenance of the cecal microflora based on the results of 16S rRNA analysis. Conclusion Dietary inclusion of three kinds of OA products all benefit broilers, but the mode of action may be different. This study provides a basis for the application of OA products used in the poultry industry.